The circulation of Anaplasma phagocytophilum ecotypes is associated with community composition of vertebrate hosts. Issue 9 (14th September 2022) - Fabri, Nannet Doreen; Sprong, Hein; Heesterbeek, Hans; Ecke, Frauke; Cromsigt, Joris Petrus Gerardus Marinus; Hofmeester, Tim Ragnvald
Abstract: Anaplasma phagocytophilum is a tick‐borne pathogen that has been detected in many tick and vertebrate species. It is among the most widespread tick‐borne pathogens in animals in Europe. The bacterium can be genetically divided into four ecotypes, which are linked to distinct but overlapping host species. However, knowledge about the transmission dynamics of the enzootic cycles of the different ecotypes is limited. Here, we quantified the link between the ecotypes of A. phagocytophilum, the different life stages of the tick Ixodes ricinus, and vertebrate host groups through a meta‐analysis. We extracted data on the mean I. ricinus burden and the A. phagocytophilum infection prevalence in both hosts and feeding I. ricinus from 197 papers on 77 wildlife species. With this information, we modeled the relative importance of different host taxonomic groups for the circulation of the different ecotypes of A. phagocytophilum in a theoretical assemblage of hosts with varying presence of red deer ( Cervus elaphus ) and densities of small mammals. We showed that the composition of the vertebrate community affects the relative abundance of different ecotypes of A. phagocytophilum in the different life stages of I. ricinus . The presence of red deer is likely to increase the infection prevalence of Ecotype 1 in ticks, while small mammal densities drive the prevalence in ticks of mainly Ecotype 3, and to a lesser extent Ecotype 1. In Europe, vertebrate communities are changing, with an increase in red deer abundance and changes in the population dynamics of small mammals. Our results suggest that these changes could imply an increase in the circulation of A. phagocytophilum and thus an increase in the risk for public and veterinary health.